Young agripreneurs in Fiji enhance production and marketing of organic virgin coconut oil - Kirwin, Litia (Technical Centre for Agricultural and Rural Cooperation, 2019)
Litia Kirwin, Founding Director of Loving Islands (Fiji) shares how her organisation is supporting the production and marketing of organic, value-added products such as organic virgin coconut oil through training.